Accounting and financial literacy o Participants in UAE Financial Markets - Ibrahim, Mohamed E; Al Haron, Esam O (Archives of Business Research, 2018)
This article seeks to explore the relationship between financial and accounting literacy and individual investors’ participation in the UAE financial markets. The article has three objectives. First, it measures the level of financial and accounting literacy among investors in the UAE financial markets. Second, it attempted to expand our understanding of how financial and accounting literacy influences investments decisions. Third, it examines the effects of demographic factors, such as age, gender, education, and nationality on investment decisions. The authors used reliability and regression analysis to explore collected data. The results indicate significant effects of the level of literacy among individual investors on thier participation in the UAE financial markets. However, no significant effects were observed for gender, educational level or nationalty.